Bright-Wits, Prince of Mogadore - Laughlin, Burren; Flood, L. L. (Leopold L.), 1881- (Salt Lake City, UT : Project Gutenberg, 2006)
"Bright-Wits, Prince of Mogadore" by Burren Laughlin and L. L. Flood is a novel written in the early 20th century. It follows the story of the clever and brave Prince Bright-Wits who embarks on a quest filled with challenges and puzzles to win the hand of Princess Azalia and secure his place in the kingdom of Parrabang. The narrative intertwines themes of wisdom, courage, and the struggle against treachery. In the tale, Bright-Wits arrives in Parrabang, where he meets Princess Azalia, only to discover that to win her heart, he must solve a series of intricate puzzles set forth by the villainous vizier Garrofat. As he navigates through various tasks such as rearranging a ruined rug, connecting fountains to their rightful gates, and more he must also contend with the dangers posed by Garrofat and his brother Doola, who seek to thwart his efforts. Ultimately, the prince demonstrates his intelligence and resilience, revealing the deceptions surrounding him and proving himself worthy of leading Parrabang alongside the princess. The dramatic conclusion ties together his trials, foiling the villains plans and confirming his destined role as a ruler. (This is an automatically generated summary.)
Release date is 2006-05-23
Produced by Library of Congress, Irma Špehar, Janet Blenkinship and the Online Distributed Proofreaders Europe at http://dp.rastko.net
Keywords: Puzzles -- Juvenile literature